Molecular prevalence, associated risk factors and phylogeny of Anaplasma marginale, Theileria ovis and T. lestoquardi in sheep from Pakistan - Tanveer, Muhammad; Farooq, Muhammad; Amjad, Muhammad; Asif, Muhammad; Kashif, Muhammad; Latif, Muhammad; Iqbal, Furhan (Elsevier Ltd, 2022)
Anaplasma marginale, Theileria ovis and Theileria lestoquardi are intracellular pathogens that infect a wide variety of animals and cause enormous economic losses worldwide. The present investigation aims to report the occurrence and the phylogeny of these pathogens infecting sheep (N = 330) from Rajanpur District in Punjab (Pakistan) by using msp1b gene for A. marginale and 18 S rRNA for T. ovis and T. lestoquardi. Results revealed that prevalence rates of A. marginale, T. ovis and T. lestoquardi were 7.3%, 6.1% and 1.2%, respectively. Four (1.2%) and one (0.3%) sheep were found to be co-infected with two and three pathogens, respectively. Risk factor analysis revealed that rams were more infected with A. marginale compared to ewes (P = 0.015). In addition, it was observed that animals located in herds having dogs and those in small herds were found more infected, respectively, with T. ovis (P = 0.001) and T. lestoquardi (P = 0.009). Phylogenetic analysis revealed that Pakistani isolates of each detected pathogens clustered together and were closely related to other Pakistani isolates and those from worldwide countries such as Iran, Iraq, Turkey, Sudan, Tanzania, South Africa, and USA. This is the first molecular study reporting the natural infection of Pakistani sheep with these three pathogens. These data need to be taken into account in order to improve the productivity of the livestock sector which is one of main sources of income in the country. © 2022 Elsevier Ltd
Keywords: Anaplasma marginale; Molecular prevalence; Pakistani sheep; Phylogeny; Theileria lestoquardi; Theileria ovis